The Correlation Between Self-Efficacy and Family Support with Adversity Intelligence in Married Female Employees at the Medan Tourism Polytechnic - Ariestina, Selly; Effendy, Sjahril; Hasanuddin, Hasanuddin (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to determine The Correlation between Self Efficacy and Family Support with Kecerdasan Adversitas for Married Female Employees of the Medan Tourism Polytechnic. The hypothesis proposed is there is a correlation between Self Efficacy and Family Support with Kecerdasan Adversitas for Married Female Employees of the Medan Tourism Polytechnic. The sample in this study amounted 43 respondents. The sampling technique using total sampling. The data collection method is a Likert scale of self efficacy, family support, and Kecerdasan Adversitas. Data analysis uses multiple linear regression analysis models. The results of this study are: 1. There is a positive and significant correlation between self efficacy and Kecerdasan Adversitas. This is indicated by the correlation coefficient (Rx1-Y) = 0.740 with p = 0.000 <0.05. Based on the results of this study, the first proposed hypothesis was declared accepted. 2. There is a positive and significant correlation between family support with Kecerdasan Adversitas. This is indicated by the correlation coefficient (Rx2-Y) = 0.668 with p = 0.000 <0.05. Based on the results of this study, the second proposed hypothesis was declared accepted 3. There is a positive and significant correlation between self efficacy and family support with Kecerdasan Adversitas. This is indicated by the correlation coefficient (Rx1.x2-Y) = 0.759 with p = 0.000 <0.05. Based on the results of this study, the third proposed hypothesis was declared accepted. It is known that the subjects of this study, Married Female Employees of the Medan Tourism Polytechnic have high self efficacy, high family support and high Kecerdasan Adversitas.